Assessment of Semi-Indoor Thermal Efficiency on Adaptive Comfort for Senior Buildings Using 3D MRT Simulation - Panraluk, Chorpech; Changnawa, Thanasarn; Shreshthaputra, Atch (Salehan Institute of Higher Education, 2026)
Adaptive comfort is a significant element in sustainable building development in hot, humid climates. The study aimed to analyze adaptive comfort in the free-running spaces of senior health and community buildings in Thailand, and propose guidelines for improving these buildings using an adaptive comfort approach. The environmental data from the automatic weather system were employed and calibrated to measure data from field surveys. Utilizing the CBE 3D Mean Radiant Temperature (MRT) Tool software for analysis and preparing data to calculate operative temperature, which was compared in ASHRAE and Southeast Asia adaptive comfort models, the study determined design and material spec modifications in three buildings for development guidelines. The findings revealed that the existing conditions of all buildings were unacceptable by nearly 20% in the rainy season and 50% in the hot season. Thermal acceptability was higher than the ASHRAE adaptive comfort model when estimated via the Southeast Asia adaptive comfort model. In these buildings, two naturally ventilated spaces did not have roof insulation, and one space did not have an overhang. All spaces received solar radiation from the south and west during the daytime. Quality materials and shading devices for MRT reduction should be prepared. This study recommends novel insights into the role of design and select materials in enhancing thermal environments for free-running spaces in senior buildings in hot, humid climates.